Sodium Butyrate as Gut Microbiota Modulators: Mechanisms of Action and Potential Clinical Applications - Literature Review and New Perspectives - Głąbień, Marta; Miłkowski, Paweł; Kuśnierz, Anna; Kusiak, Karolina; Aleksandrowicz, Daria; Wieczorek, Olga; Jakubczak, Zofia; Zimniak, Maria Weronika; Śliwiak, Patryk; Kondratowicz, Aneta (Quality in Sport, 2024)
Introduction Sodium butyrate is an organic chemical compound belonging to sodium salts, which has the potential to be used in anticancer therapy. It reduces inflammation of the intestinal mucosa and promotes the development of beneficial intestinal flora, thanks to which it helps maintain homeostasis. Therefore, butyrate reduces the risk of developing colon cancer or reverses pathological changes occurring under the influence of this cancer. Scientific studies have also shown a beneficial effect of butyrate on the side effects of anticancer treatment - chemotherapy and radiotherapy. A proper diet also has a beneficial effect on the production of endogenous butyrate and reduces the risk of developing colon cancer. It is recommended to use a Mediterranean diet, rich in dietary fiber, highly unsaturated fatty acids and fresh vegetables and fruits. It is recommended to avoid highly processed products, rich in simple sugars and saturated fatty acids, and to limit the consumption of red meat. Materials and methods This article is based on the literature found in the PubMed and other scientific databases from the period of 1978-2023 with the use of key words such as “butyrate” “sodium butyrate” “colon cancer” “anticancer treatment” “intestinal microbiota” “Mediterranean diet” Conclusion Sodium butyrate is a potential substance that, through its properties, may support the treatment of colorectal cancer. Additionally, the use of an appropriate diet has a positive effect on the intestinal microflora, allowing the action of sodium butyrate and reducing the risk of colorectal cancer.